Pengembangan Multimedia Interaktif Berbasis Inkuiri untuk Praktikum Virtual pada Materi Bioteknologi di SMA - Suryanda, Ade; kurniati, Tri Handayani; Damayanti, Shanti (Program Studi Pendidikan IPA, FKIP Universitas Pancasakti (UPS) Tegal, 2020)
Biotechnology is one of the subject matter that is difficult for students to understand. This difficulty is caused by biotechnology to study many complicated and abstract processes for students, one of which is about genetic engineering. Appropriate learning methods such as practicum are needed so that learning is more effective. There are limitations in carrying out genetic engineering practicum activities at the high school level, so we need a solution to overcome these limitations. The use of interactive multimedia based on inquiry is expected to present material in the form of practicum virtually so that the concept of genetic engineering becomes easier to understand. The purpose of this study is to develop interactive multimedia based on inquiry for virtual practicum on biotechnology materials in high school. Inquiry-based interactive multimedia is media that contains two or more elements of the media that are designed systematically, interestingly, and packaged interactively to stimulate students to think scientifically and skillfully find answers that begin with curiosity. The method used is a research and development method. This study uses an instrument in the form of a questionnaire analysis of needs and interviews, as well as a feasibility test questionnaire on experts, teachers, and students. The results showed that an interactive multimedia base on inquiry product had been successfully developed with an average percentage of all product feasibility tests of 83.1%, meaning that the product was included in the criteria very well and was suitable for use as an alternative media in learning biology.